DETERMINING THE FACTORS THAT DRIVE TWITTER ENGAGEMENT-RATES - Semiz, Gulsah; Berger, Paul D. (Archives of Business Research, 2017)
ABSTRACT Twitter is one of the most important social networks and is a micro-blogging site where users send short messages, often called, “tweets.” In this paper, we explore the determination of variables that affect the engagement rate of a tweet. We utilize data during the first 11 months of 2016 from TurkishWIN’s Twitter Handle, and use Excel and SPSS to analyze several variables with respect to their impact on engagement rate. These variables includes the day of the week, the time of day, the length of the tweet, the number of mentions, the number of hashtags, and the language of the tweet among other variables. Using stepwise regression analysis, we find that several variables have a highly significant relationship to the engagement rate of a tweet. We discuss each significant variable in terms of the exact relationship it has with tweet engagement, and the implications of these relationships. Lastly, we note the limitations of our study and suggested directions for future research.